Multi-omics-based identification of SARS-CoV-2 infection biology and candidate drugs against COVID-19. (November 2020) - Barh, Debmalya; Tiwari, Sandeep; Weener, Marianna E.; Azevedo, Vasco; Góes-Neto, Aristóteles; Gromiha, M. Michael; Ghosh, Preetam
Abstract: SARS-CoV-2 has ushered a global pandemic with no effective drug being available at present. Although several FDA-approved drugs are currently under clinical trials for drug repositioning, there is an on-going global effort for new drug identification. In this paper, using multi-omics (interactome, proteome, transcriptome, and bibliome) data and subsequent integrated analysis, we present the biological events associated with SARS-CoV-2 infection and identify several candidate drugs against this viral disease. We found that: (i) Interactome-based infection pathways differ from the other three omics-based profiles. (ii) Viral process, mRNA splicing, cytokine and interferon signaling, and ubiquitin mediated proteolysis are important pathways in SARS-CoV-2 infection. (iii) SARS-CoV-2 infection also shares pathways with Influenza A, Epstein-Barr virus, HTLV-I, Measles, and Hepatitis virus. (iv) Further, bacterial, parasitic, and protozoan infection pathways such as Tuberculosis, Malaria, and Leishmaniasis are also shared by this virus. (v) A total of 50 candidate drugs, including the prophylaxis agents and pathway specific inhibitors are identified against COVID-19. (vi) Betamethasone, Estrogen, Simvastatin, Hydrocortisone, Tositumomab, Cyclosporin A etc. are among the important drugs. (vii) Ozone, Nitric oxide, plasma components, and photosensitizer drugs are also identified as possible therapeutic candidates. (viii) Curcumin, Retinoic acids, Vitamin D, Arsenic, Copper, and Zinc may be the candidate prophylaxis agents. Nearly 70% of our identified agents are previously suggested to have anti-COVID-19 effects or under clinical trials. Among our identified drugs, the ones that are not yet tested, need validation with caution while an appropriate drug combination from these candidate drugs along with a SARS-CoV-2 specific antiviral agent is needed for effective COVID-19 management. Graphical abstract: Image 1 Highlights: SARS-CoV-2 shares Influenza, EBV, HTLV-I, Measles, and Hepatitis virus infection pathways. SARS-CoV-2 also shares Tuberculosis, Malaria, and Leishmaniasis infection pathways. mRNA splicing, cytokine and IFN signaling, and ubiquitin are important pathways. Betamethasone, Estrogen, Statin, Tositumomab, Cyclosporin A are top candidate drugs. Ozone, Nitric oxide, plasma components, and photosensitizer drugs are also important against COVID-19. Curcumin, Retinoic acids, Vitamin D, Arsenic, Copper, and Zinc are candidate prophylaxis agents.